If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 18p = -19 Combine like terms: p + 18p = 19p 19p = -19 Solving 19p = -19 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '19'. p = -1 Simplifying p = -1
| 7m+5-5(m-3)=5(m+4)-3m | | n=2+1.5p | | 125-7+4(6*2)=166 | | 3x-7+2(3x+1)=-5(x+3) | | 125-7+4(6*2)= | | 8(3x-7)+12x= | | 7x+6(2x-9)=174 | | 2x+16=3x+6 | | 12n-2n+2n-6n-4n=16 | | (9-z)(5z-7)=0 | | 5x+x+6+3x+3=4x+6 | | -14x+2x+38=11x-6 | | -0.25x-4+0.75x=0.5x+1 | | y+1=29 | | 6(x+4)+2=-10(x-6)-6 | | 10-(4x-8)=2 | | 2(y+9)=-2(4y-2)+2y | | 8(6x-2)+10x= | | 7x-4(3x+5)-6= | | 2(x+2)=-5+5x | | 5(h-12)=8h | | 0.5t-10v=6 | | 17k+k+2k+2k-21k=18 | | 3m^2-10+8=0 | | Y=(x^2-3x+5)-(-4x^2+8x+9) | | 8x+10=-5x+5 | | t=c-12.6 | | (9b-b)-b | | 2(2+3z)=8-2(4z+5) | | -2(5+6a)+16=-90 | | 2x+6(6x-14)=106 | | 5g+100=11g-50 |